Treino em esteira com suporte parcial de peso associado à estimulação elétrica funcional melhora a marcha de hemiparéticos crônicos e efeitos da inclinação da esteira na marcha de sujeitos hemiparéticos - Lindquist, Ana Raquel Rodrigues (2005)
The purpose of this study was to evaluate the effect of the combined use of functional electrical stimulation (FES) and treadmill training with body weight support (BWS) in walking functions and voluntary limb control in chronic hemiparetic patients. Eight hemiparetic individuals (mean age, 56.6 ± 10.26 years) were evaluated in the present clinical trial. The stroke interval was 17.3 ± 10.9 months. The stroke etiology of the subjects was ischemia (75%) or haemorrhage (25%) in the middle cerebral artery region. An A1-B-A2 single-case study design was applied. Phases A1 and A2: three weeks of gait training on a treadmill with body weight support, and phase B: three weeks of treadmill training plus FES. FES was applied to the peroneal nerve to improve ankle dorsiflexion during the swing phase and heel strike on the initial floor contact. Stroke Rehabilitation Assessment of Movement (STREAM, 0-60) was used to assess motor recovery. Kinematical analysis was used to assess cycle length (m); cycle duration (s); gait velocity (m/s); stance duration (s); swing duration (s) and cadence (steps/min). The results showed substantial improvement in the motor functions during phase B (from 54.9% to 71.0%). The space-temporal variables of cycle duration, stance and cycle cadence as well as cycle symmetry presented improvements when compared to treadmill training with BWS but without FES (p<0.01). The combined use of FES and treadmill training with BWS promoted an improvement in the motor recovery and gait pattern of hemiparetic subjects and could be used during gait rehabilitation. The purpose of this study was to investigate the effects of uphill treadmill inclination in the gait of ambulatory subjects with hemiparesis. Fourteen individuals (mean age 64.3±14.56 years) were evaluated in the present trial. The stroke etiology of the subjects was supratentorial ischemia (12 cases) or haemorrhage (2 cases). Gait analysis was performed during each experimental condition (floor walking and uphill treadmill walking of 0, 2, 4, 6 and 8%). The space-temporal variables, gait line, cyclogram, force graphs and vertical ground reaction forces during initial contact, midstance and toe-off, and muscular activity were recorded by Infotronic Ultraflex System. Muscular activity recordings were obtained for the following muscles on the subjects paretic side: tibialis anterior, medial belly of gastrocnemius, biceps femoris, vastus lateralis, vastus medialis, gluteus medius and erector spinae. Heart rate was also monitored during each experimental condition. The results showed that uphill treadmill improved the heart rate from 82.6±11.0 bpm to 97.7±20.2 bpm as the treadmill inclination improved to 8%. Spacetemporal variables were not significantly affected by the uphill walking while velocity remained steady. EMG amplitude of gastrocnemius decreased while vastus lateralis and biceps femoris increased with slope. We conclude that treadmill inclination would have some beneficial effect on the subjects general fitness and could be used during stroke rehabilitation when the patient motor condition does not allow the increase of gait velocity. However, gait ability in stroke patients changes within certain limits during uphill treadmill.